The Development of Electronic Practicum Modules at Electronic Course for Physics Education Program - Muhammad Amin Said; Muhammad Arsyad; Muh. Tawil (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This study aimed to design a practicum module in electronics courses. The researcher initially carried out the developed module to analyze the level of validity and students’ responses to the electronic practicum module that the researcher had created. The module developed was validated by two experts. The subjects of this research were students of the Physics Education Program at the Muhammadiyah University of Makassar in the odd semester in the academic year of 2019/2020. This research employed a Research and Development (R&D) design. The development was carried out using the 4D model with four stages: Define, Design, Develop and Disseminate proposed by Thiagarajan. The results showed that the expert assessment of the electronic practicum module that had been developed using the Gregory test closeness model obtained a strong relevance level because it had an internal consistency coefficient of 100% and was declared to meet the eligibility criteria (valid). The percentages of students’ responses in the three indicators (interested in using the module, easy to understand the module content and easy-to-understand module language) were 83%, 81 %, and 81%, respectively. Based on the description above, it can be concluded that the electronic practicum module developed is declared valid, and students respond well to the use of the electronics practicum module.